Building the Character of MAN Sorong Students Through the Habit of Zakat Fitrah in the Month of Ramadan - Irjayanti, Wahyu Puspita (Indonesian Journal of Islamic Educational Review, 2025)
This study analyzes the implementation of zakat fitrah habituation at MAN Sorong and its impact on student character development within the Islamic character education framework. Zakat fitrah, as a fundamental Islamic obligation, serves not only as worship but also as a critical vehicle for fostering moral development and social responsibility. This qualitative case study employed participatory observation, in-depth interviews with Fiqh teachers, student council supervisors, and mosque takmir, and documentation of zakat fitrah activities involving 44 students from grades XI and XII. The findings reveal that zakat fitrah habituation operates through five key implementation strategies: intensive socialization and education, structured collection mechanisms, transparent distribution processes, exemplary leadership modeling, and strategic institutional collaboration with local mosques. The program significantly enhances multiple dimensions of character development, including social awareness, empathy, gratitude, discipline, responsibility, and collaborative skills. Students developed enhanced self-confidence, civic identity, and leadership capabilities through direct involvement in collection and distribution processes. The experiential learning approach creates meaningful community connections while reinforcing Islamic values and moral principles. Implementation challenges including insufficient awareness, resource constraints, and varying student economic circumstances were successfully addressed through intensive socialization programs, creative fundraising initiatives, and strategic partnerships with zakat institutions. The multi-stakeholder collaboration model proved effective in creating sustainable character development outcomes while strengthening school-community relationships. However, the study acknowledges limitations, including single-site design and qualitative methodology constraints, which limit generalizability. The research concludes that systematic integration of zakat fitrah habituation within Islamic educational settings provides an effective framework for comprehensive character education, producing students with increased empathy, social responsibility, and civic engagement. These findings have significant implications for Islamic educational institutions seeking evidence-based approaches to character development.